MENINGKATKAN KEMAMPUAN KOGNITIF ANAK PADA BENTUK GEOMETRI - Yuniawati, Rani; Nuraeni, Aneu; Ambarwati, Ratih (Ibtidaiyyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Kindergarten is a form of preschool education unit that is held before the basic education level. Creativity is an individual's ability in the form of new ideas, methods, processes or products that are innovative and imaginative. One activity that can increase children's creativity is printing activities from natural materials. One thing that is developed is the cognitive ability of geometric shapes. Low ability to learn geometric shapes is a problem faced by teachers in Group A RA Baiturrahman Tasikmalaya. This research aims to develop and improve students' cognitive abilities in geometric shapes using environmental media. This research uses Classroom Action Research (PTK) which is carried out in two cycles, with each cycle containing planning, implementation, observation and reflection. In cycle I the results were 50% and in cycle II the results were 82,05%. These results show that this research was successful because it exceeded the research indicator target of 80%. The results of this research show that using natural media as a learning resource can be said to be successful in improving geometric shape abilities. Based on this research, it is recommended that all teachers can provide learning about geometric shapes that is interesting and fun for children. Teachers should also be able to create a comfortable and enjoyable learning environment for children. ABSTRAK TK/RA merupakan salah satu bentuk satuan pendidikan prasekolah yang diselenggarakan sebelum jenjang pendidikan dasar. Kreativitas merupakan kemampuan individu yang berupa gagasan, metode, proses, atau produk baru yang bersifat inovatif dan imajinatif. Salah satu kegiatan yang dapat meningkatkan kreativitas anak adalah kegiatan mencetak dari bahan alam. Salah satu yang dikembangkan adalah kemampuan kognitif bentuk geometri. Kemampuan belajar bentuk geometri yang rendah menjadi masalah yang dihadapi guru di Kelompok A RA Baiturrahman Tasikmalaya. Penelitian ini bertujuan mengembangkan serta meningkatkan kemampuan kognitif siswa pada bentuk geometri dengan menggunakan media alam sekitar. Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, dengan masing-masing siklus terdapat perencanaan, pelaksanaan, observasi, dan refleksi. Pada siklus I diperoleh hasil 50% dan pada siklus II diperoleh hasil 82,05%. Dengan hasil tersebut menunjukkan bahwa penelitian ini berhasil karena melebihi target indikator penelitian sebesar 80%. Hasil penelitian ini menunjukkan bahwa dengan media alam sebagai sumber belajar dapat dikatakan berhasil dalam rangka meningkatkan kemampuan bentuk geometri. Berdasarkan penelitian tersebut disarankan pada semua guru dapat memberikan pembelajaran bentuk geometri yang menarik dan menyenangkan anak. Guru juga hendaknya mampu menciptakan lingkungan pembelajaran yang nyaman dan menyenangkan bagi anak.